Clinical features and outcomes of epidermolysis bullosa in thai children: A 20-Year review from a Tertiary Care Center - Niltem, Ekamon; Rujimethapass, Nootchanard; Sukhneewat, Chonnakarn; Limpongsanurak, Wanida; Singalavanija, Srisupalak (Archives of Community Medicine and Public Health, 2022)
Background: Epidermolysis Bullosa (EB) is a heterogeneous genetic disorder with skin fragility. Only a few cases have been reported in Thailand. This study aims to determine the clinical characteristics, complications, and outcomes of EB stratified by subtype. Methods: A retrospective single-center study of EB patients at the Dermatology Unit, Queen Sirikit National Institute of Child Health, was reviewed from January 1, 2002, to December 31, 2021. Diagnosis is based on clinical manifestations and some skin biopsies. Results: There were 38 enrolled patients, age range from 0 to 25 years with a male-to-female ratio of 1.1:1. Family history of EB and consanguineous marriage were found in 6 cases and 2 cases, respectively. The most common type of EB was dystrophic EB (DEB) (26 cases) (68.4%), including recessive DEB in 15 cases (39.5%) and dominant DEB in 11 cases (28.9%). Other types were EB simplex in 10 cases (26.3%) and junctional EB in 2 cases (5.3%). Common complications were cutaneous bacterial infection (39.5%), anemia (31.6%), failure to thrive (18.4%), and protein energy malnutrition (15.8%). Musculoskeletal (21.1%), gastrointestinal (13.2%), and eye complications (7.9%) were exclusively found in DEB. Nineteen patients (50%) received regular follow-ups with a median duration of 9 months (range = 0.5 to 248 months). The mortality rate was 31.6% (6/19). Five cases died from bacterial sepsis, while one case died from metastatic squamous cell carcinoma. Conclusion: DEB is the most common type of EB in Thai children, and bacterial sepsis is the predominant cause of death. Further multicenter and molecular genetic studies are recommended for a definite diagnosis.